PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA TOPIK GAYA DI KELAS IV SD SWASTA FREE METHODIST 2 MEDAN - Fitri Silia Nengsih Kesuma Dewi; Andi Wapa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Bakti Indonesia, 2023)
This research is motivated by the low student learning outcomes in the Natural Sciences subject on the topic of Style, this is evidenced by the pre-cycle learning outcomes, out of 28 students only 6 students or (21.43%) complete, while 22 students or (78.57%) ) is not complete. The purpose of this research is to find out: How can the application of the disclosure method improve student learning outcomes in learning the topic Natural Science in Grade IV students at SD Free Methodist 2 Medan? The results of this study indicate that student learning outcomes experienced a very significant increase, in cycle I, 15 people or (53.57%), cycle II, 24 people or (85.71%). The conclusion of this study is that the application of the demonstration method can improve student learning outcomes in science learning on the topic Gaya in class IV of SD Free Methodist 2 Meda